Os níveis de desenvolvimento do pensamento geométrico: o aprendizado do conteúdo de polígonos numa perspectiva do modelo Van Hiele - Nagata, Rosenilda de Souza (2016)
This work studies the van Hiele model, the levels of development of geometric thinking and its learning phases. Using this knowledge, we prepared a Research Instrument to identify the Level of Development in Geometric Thinking (Levels of van Hiele) of Middle School students, related to contents of Polygons. We have applied this Research Instrument to 237 students from a public school (state) in Curitiba, and we made an analysis of the acquired data. We have improved the Instrument’s questions so that it can be used by teachers during the class. Helping to identify to which level content the student belongs, related to the proposed.